Workload and work professionalism against AKIP : accountability for performance of government agencies - Heru Kreshna Reza; Dennis Rydarto Tambunan; Kurniati Karim; Melly Susanti (Journal of Economics and Business Letters, 2021)
Accountability Performance Of government agencies is a manifestation of the obligation of a government agency to account for the success or failure of implementing programs and activities that have been mandated by stakeholders . To avoid the failure of the performance levels required by the proper distribution of work and professionalism in complete assigned tasks. The purpose of this study was to determine the relationship between workload and professionalism on the Performance Accountability of Government Agencies (AKIP). The population in this study were all State Civil Apparatus (ASN) atInspectorate the Bengkulu City. Sample data as many as 75 State Civil Apparatus. The Technique analysis data uses a moderating effect test, namely the quasi-moderated absolute difference test of Multiple Linear Regression (multiple linear regression) using the IBM SPSS Statistics 22 statistical program. The results of this study show that there is a significant relationship between workload and professionalism on the Performance Accountability of Government Agencies in Bengkulu City Inspectorate. It is proven by the significance value in the partial test between workload and professionalism of 0.000. The t-count value in thetest partial of the workload variable is 3.100 > 1.66 and the t-count value on the professionalism variable is 4.517. The results of the test partial of these two variables independent have a significant relationship to the Performance Accountability of Government Agencies (AKIP). Simultaneous test results on the variables independent (workload and professionalism) obtained significant results, namely 0.000. Based on the comparison of theF value calculated with the Ftable, the value calculated F greater than the value of F Table ie 21.380 > 3.09 .